PENCEGAHAN KEKERASAN DI KALANGAN PELAJAR SMP NEGERI 15 KOTA KUPANG DALAM PERSPEKTIF HUKUM PIDANA - Yohanes Leonardus Ngompat; Dwityas Witarti Rabawati; Filemon Fridolino Ngebos; Eka Cahyo Saputra; Alexander Jorgi; Petrus Faot (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Violence in school settings remains a common problem, whether in the form of physical, verbal, or digital (cyberbullying) violence. This phenomenon runs counter to the goals of national education, which aim to create a safe and conducive learning environment. This community service activity aims to enhance the legal understanding and awareness of students at SMP Negeri 15 Kota Kupang regarding the prevention of violence from a criminal law perspective. The method employed involves legal outreach through the stages of preparation, implementation, and evaluation using an educational outreach approach. The material presented covered forms of violence, their impact on victims, and legal consequences based on the Criminal Code and Law No. 11 of 2012 on the Juvenile Criminal Justice System. The activity was evaluated through interactive discussion sessions to measure students’ level of understanding before and after the activity. The results of the activity showed that most students previously did not understand that actions such as hitting, teasing, threatening, and bullying could constitute illegal acts. Through the students’ active participation in the discussion sessions, there was an increase in their understanding of the impacts of violence, legal consequences, the importance of respecting others’ rights, and peaceful conflict resolution. This activity demonstrates that an educational and preventive approach through legal awareness campaigns is effective in building students’ legal awareness and supporting the creation of a safe, comfortable, and violence-free school environment.